A health benefit and cost-effectiveness analysis of pneumococcal conjugate vaccination program in Nigeria - Idris, Israel O.; Badejo, Okiki O.; Ochagu, Victor; Lamidi, Sheriff A.; Gavkalova, Nataliia (International Journal Of Community Medicine And Public Health, 2020)
Background: Nigeria ranks third just behind India and China in the global disease burden of pneumococcal disease. The current sustainability approach for an affordable pneumococcal conjugate vaccine (PCV) for the national immunization program from 2014 till 2025 involves a cost sharing plan funded with a 75% financial support from GAVI and a subsidy from Pfizer pharmaceuticals. There is a strong need to generate evidence on the cost-effectiveness of the national PCV program in Nigeria from 2014-2025 and beyond 2025. Methods: The following parameters (demography, disease burden, health services utilization and costs, vaccination coverage, vaccine efficacy, and vaccination costs) were used in a static cohort model to estimate the total cost, health and economic benefit, and cost-effectiveness of the implementation of PCV vaccination program, compared with no PCV vaccination among under-five children in Nigeria from 2014-2025 and from 2026-2033. A sensitivity analysis was conducted to evaluate the robustness of the data used. Results: The national PCV vaccination program would have an approximated 31.4% and 30% reduction of the total burden of pneumococcal diseases over the period of 2014-2025 and 2026-2033 respectively. One-way sensitivity analysis reveals vaccine efficacy as most sensitive parameter followed by disease incidence rate and treatment cost. Removal and addition of DTP3 and 3+1 (measles vaccine) dose respectively resulted to a similar ICER from both. Conclusions: The estimated ICER suggests that the national PCV program in Nigeria will be cost-effective post 2025 era. In addition, it is recommended for policy-makers adoption considering the budget and equity impact of the intervention in Nigeria.